Survival Analysis of Food Security in Asian Countries - Fitrianto, Anwar (2005)
This study focuses on using the survival analysis on food security application. The technique examines the effects of covariates on food insecurity among Asian countries in the period of 40 years since 1961. The analysis is carried out in order to determine the 'warning sign' of food insecurity condition. The data sources are from FA0 and World Bank online database which include some particulars of 32 Asian countries. It is observed that 21 of 32 (65.62%) countries experienced insecurity food condition. The remaining are censored observations (34.38%). The stepwise Cox's regression is used to select among the 24 independent covariates that are deemed to be significant contribution to the model. Initial run of the SAS code finds that six covariates are significant. Based on the adopted model, at each time point, the West Asian region are found to be more likely to have insecurity food condition compared to those countries in the other regions. Furthermore, the occurrence of food security for East Asia countries are more likely than for those in the other region. Meanwhile, it can also be seen that countries in Lower-middle income group are more likely to reach insecurity food condition than those in the other group. The analysis also shows that the high income countries have high risk of exposure to insecurity food condition. Since Cox regression analysis has the basic assumption of proportionality, the model was tested whether it meets this condition. We use graphical method and formal test of this assumption . In the presence of ties, the ties-handling method of Breslow, Efron, Exact, and Discrete are compared with respect to Wald statistics, parameter estimate, the hazard ratio, and p-value. The availability of the determined dataset as in allows assessing categories of food insecurity; Low, Medium, or High, which is useful to describe the nature of the food insecurity conditions. Based on the analysis, we are able to find variables that play important role on each stage of food insecurity condition of each country.